Dimorphic brain region regulation of microglia morphology and behavioral implication focus on the crosstalk between glucocorticoid and adenosine a2a receptors - Duarte, Joana Filipa Mendes (2016)
Dissertação de Mestrado em Bioquímica, apresentada ao Departamento de Ciências da Vida da Faculdade de Ciênicas e Tecnologia da Universidade de Coimbra